An RFID grouping proof protocol exploiting anti-collision algorithm for subgroup dividing. (19th March 2010) - Leng, Xuefei; Lien, Yuan-Hung; Mayes, Keith; Markantonakis, Konstantinos
Verifying that several RFID tags are all present in a group poses specific challenges that have generated great interest in the academic community. As the number of tags becomes large, the unreliability of radio wave communication could potentially cause possible high failure rates to the existing grouping proof. In this paper, we propose a way of grouping proof, which uses the dynamic binary tree anti-collision algorithm to subgroup the tags. This paper combines the 'Yoking Proof' idea and the 'Select-Response' mode from previous publications. The 'Yoking Proof' is generated between subgroups and within each subgroup, and as a result, the failure rates are greatly reduced. The 'Select-Response' mode is used for subgroup verification.